Upaya Meningkatkan Prestasi Belajar Siswa Kelas IX-D melalui Model Pembelajaran Konstruktivistik pada Mata Pelajaran IPS - Ta'awan Ta'awan (Jurnal Pendidikan : Riset dan Konseptual, 2018)
Necessary effort to create economic teaching that can be fun for students to learn at every level in Holistic and Integration. For that, it needs to be developed with reference to Constructivistic approach, since this approach quite rapidly in some developed countries and has given a positive learning outcomes for students. Teacher need to understand what is meant by the constructivist approach, in addition to understanding how to design the learning economy that is based on the approach Constructivistic. Expended the teacher to implement learning model economy that favores by students. Classroom action reserach conducted in three cycles with the steps of planning, action, observation, and reflection. The result showed that the average student is taught using constructivist approach result are better that students who are taught by the ordinary teaching materials. On average cycle 1 daily deuteronomy 66, in the cycle 2 average daily deuteronomy 76 and in cycle 3 deuteronomy daily average increased to 84. From the data analysis it turns out students who taught with more constructivist approach is effective in increasing motivation and achievement learn when compared with students who are not taught by constructivistic approach